2006
DOI: 10.1186/1475-2875-5-94
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance to sulphadoxine-pyrimethamine in Plasmodium falciparum malaria in Mlimba, Tanzania

Abstract: BackgroundSulphadoxine-pyrimethamine (SP) has been and is currently used for treatment of uncomplicated Plasmodium falciparum malaria in many African countries. Nevertheless, the response of parasites to SP treatment has shown significant variation between individuals.MethodsThe genes for dihydrofolate reductase (dhfr) and dihydropteroate synthase (dhps) were used as markers, to investigate parasite resistance to SP in 141 children aged less than 5 years. Parasite DNA was extracted by Chelex method from blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 40 publications
(50 reference statements)
1
24
1
Order By: Relevance
“…Our study in Hale found 581G in 54% of isolates (n = 84). In Ifakara[31] in 1997, 27.8% of isolates (n = 18) were found to carry the mutant while Mlimba[32] and Mbeya[33] had low prevalence of 1.6% (n = 128) and 1.2% (n = 81) respectively. Surveys in Butimba (n = 57), Mlimba (n = 59), Kyela (n = 67), Masasi (n = 73), Mkuzi (n = 127), reported no 581G mutations [8], and similarly a survey in Muheza (n = 28) [34].…”
Section: Resultsmentioning
confidence: 98%
“…Our study in Hale found 581G in 54% of isolates (n = 84). In Ifakara[31] in 1997, 27.8% of isolates (n = 18) were found to carry the mutant while Mlimba[32] and Mbeya[33] had low prevalence of 1.6% (n = 128) and 1.2% (n = 81) respectively. Surveys in Butimba (n = 57), Mlimba (n = 59), Kyela (n = 67), Masasi (n = 73), Mkuzi (n = 127), reported no 581G mutations [8], and similarly a survey in Muheza (n = 28) [34].…”
Section: Resultsmentioning
confidence: 98%
“…The presence of IgM suggests that the women were still infected despite the IPTp they were receiving during pregnancy or that the parasites were possibly resistant to SP to some degree [66]. However, SP-IPTp has recently been shown to clear parasitaemia in asymptomatic women [67].…”
Section: Discussionmentioning
confidence: 99%
“…Malaria‐causing Plasmodium species account for more than 200 million new infections each year, resulting in roughly 500 000 annual deaths, with the burden disproportionally skewed toward children under five years of age . Emergence of resistance to first‐line treatments, including artemisinin combination therapies, continues to undermine the considerable progress made in eradicating infection, and puts into sharp focus the critical need to drug new targets with novel scaffolds . The Pathogen Box contains 125 compounds which possess antiplasmodial activity, many of which were identified from phenotypic screening of the GSK Tres Cantos Anti‐Malarial Set (TCAMS) …”
Section: Malariamentioning
confidence: 99%